Төгрөг нуурын нүүрсний ордын эртний ургамлын үр тоосонцрын олдворын шинэ мэдээлэл - Н.Одгэрэл; Н.Ичинноров; Н.Байгалмаа; Г.Цолмон; Ц.Нямхишиг (Geological Issues, 2023)
The palynomorph study of Tugrug nuur coal deposit is important for stratigraphycal classification of sedimentary basins. This deposit is located in Choyr-Nyalga basin in Eastern Mongolia. Outline of geology and chemistry of rock, paleobotany are reported by previous studies. The present paper reports the first palynological analyses in this area. Tugrug nuur deposit is hosted in syncline structure, divided into two parts, Takhilt and Khovil. Lower Cretaceous deposits arc classified into as two formations Lower Dzuunbayan (K1dz1) and Upper Dzuunbayan (K1dz2). During field servey 2012, 5 samples collected from Upper Dzuunbayan formation of the Tugrug nuur deposit were analyzed for palynomorph. Palynomorph in Takhilt part is characterized by abundant pollen of Gymnospermae, amounting 61% of the total number the assemblage. The Gymnosperms pollen grains are presented by species of Piceapollenites, Cedripites, Podocarpidites, Protoconiferus, Ginkgocycadophytus, Cerebropollenites, and Inaperturapollenites. The spores are mostly represented by the genera Cyathidites, Lycopodiumsporites, Gleicheniidites and Dictyotriletes. In the Khovil part, 55% of the spore assemblage is Leptolepidites, Cyathidites, Sphagnumsporites, and Stereisporites, while 47% of the pollen grains are Piceapollenites, Podocarpidites, Inaperturapollenites. Gingkocycodophytus, and Cycadopites. Further detailed palynological analyses for age postulation of coal-bearing unit are necessary in this area.